Investigating the Effects of Video-Based Learning on Students’ Cognitive Load - HOUICHI, Asma (جامعة مستغانم, 2022)
Technology has affected all aspects of our lives including the way of learning and teaching. Nowadays, it plays a great role in facilitating many activities and developing multiple skills. In the field of foreign languages teaching and learning, in particular, a number of approaches, methods, and techniques have brought about a myriad of significant changes along with the evolution of technology so that teachers may benefit from the use of new trends in their classroom. These trends, particularly those related to multimedia, can be harnessed to improve the efficiency of foreign language teaching and learning by lessening the load students experience while processing new information. In this connection, the present study aims to investigate the effects of integrating video-based learning as a tool to minimize the cognitive overload of EFL first-year LMD students’ compared to text-based learning at Si El Haoues University Center, Barika. The study entailed a quasi-experimental design via a mixed-methods approach. To carry out this research, the sample included 101 students conveniently selected: 50 and 51 participants for each experimental and control group, respectively. The former was taught using video-based learning, while the latter was taught via text-based learning. To gather the required data, four tools were used; a post-test was administered in order to measure the participants' academic performance; a self-reported questionnaire (NASA-TLX) was given to measure the participants' mental workload they have experienced while watching the video; a post-treatment questionnaire was administrated to the experimental group to delve into their perceptions of the treatment and, lastly, reflective journals were conducted by the researcher throughout the experiment to journal whatever related to the experiment. For five weeks with six sessions of experimentation, post-test findings demonstrated a significant difference between the students’ level of cognitive load, and thereby their academic performance. Furthermore, members of the experimental group perceived the treatment as highly satisfying. The interpretation of the findings indicated that there was a relationship between students’ understanding of the content presented via videos and their level of cognitive load. As matter of fact, the researcher contends that videos represent an effective tool to deliver courses while seeking to reduce students’ cognitive overload and to improve their academic performance.
Keywords: cognitive load, EFL learners, video-based learning, text-based learning